Two Sets of Metal Organic Frameworks along the Lanthanide Series Constructed by 2,3-Dimethylsuccinate: Structures, Topologies, and Strong Emission without Ligand Sensitization - Gomez, Germán Ernesto (2013)
Reactions in aqueous solution under hydrothermal conditions between (±)-2,3-dimethylsuccinic acid and lanthanide chlorides lead to two different isostructural types with chemical formulas [Ln2(C6H8O4)3(H2O)2] Ln(III) = Pr−Eu (except Pm) (Type I, compounds 1−4) and [Ln2(C6H8O4)3] Ln(III) = Tb−Yb (except Tm) (Type II, compounds 5−9). The crystal structure has been solved for the Pr (1)-, Sm (3)-, and Ho (7)-containing compounds by means of single-crystal XRD methods, whereas powder XRD Rietveld refinement was used for the rest of the MOFs. Compounds 1−4 crystallize in the triclinic space group P1̅, whereas compounds 5−9 belong to the tetragonal space group P43212. Type I and II compounds are 3D frameworks consisting of chains of [LnO8(H2O)] or [LnO8] polyhedra, respectively, linked by dimethylsuccinate anions, giving rise to I1 O2 connectivity. All the compounds were characterized by X-ray diffraction, variable-temperature Fourier transform infrared spectroscopy, and thermal analysis. An exhaustive topological study was performed in comparison with other related compounds. The photoluminescent (PL) properties for compounds 3, 4, and 5 have been also explored, indicating that a metal-centered luminescent process takes place.